My Lookalike at the Krishna Temple : Poems - Osherow, Jacqueline (Book collections on Project MUSE., 2019)
the author considers expressions of spirituality from cultures all over the world and investigates previously unexplored aspects of her relationship to Judaism and Jewish history. While some poems reflect on practitioners of self-imposed isolation, from the monks in Fra Angelico's frescoed cells to Emily Dickinson to the Kotzker Rebbe, others explore topics as varied as architecture, geometry, faith, war, and genocide. The author finds beauty in Joseph's dreams, the euphony of crickets, and the gamut of symmetries on display in the Alhambra.